Pathology and virology of natural highly pathogenic avian influenza H5N8 infection in wild Common buzzards (Buteo buteo) - Caliendo, Valentina; Leijten, Lonneke; van de Bildt, Marco W. G.; Fouchier, Ron A. M.; Rijks, Jolianne M.; Kuiken, Thijs (Scientific reports, 2022)
Highly pathogenic avian influenza (HPAI) in wild birds is a major emerging disease, and a cause of increased mortality during outbreaks. The Common buzzard ( Buteo buteo ) has a considerable chance of acquiring the infection and therefore may function as bio-sentinel for the presence of virus in wildlife. This study aimed to determine the virus distribution and associated pathological changes in the tissues of Common buzzards that died with HPAI H5 virus infection during the 2020–2021 epizootic. Eleven freshly dead, HPAI H5 virus-positive Common buzzards were necropsied. Based on RT-PCR, all birds were systemically infected with HPAI H5N8 virus, as viral RNA was detected in cloacal and pharyngeal swabs and in all 10 selected tissues of the birds, with mean Ct values per tissue ranging from 22 for heart to 32 for jejunum. Based on histology and immunohistochemistry, the most common virus-associated pathological changes were necrotizing encephalitis (9/11 birds) and necrotizing myocarditis (7/11 birds). The proventriculus of two birds showed virus-associated necrosis, indicating tropism of this virus for the digestive tract. Our advice is to collect at least a miniset of samples including brain, heart, liver, and spleen, as these tissues were positive both by RT-PCR and for virus-antigen-associated lesions.